2022
DOI: 10.21608/ejhc.2022.264766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Skin-to-Skin Contact between Mothers and Newborns at Birth on Temperature, Oxygen Saturation, and Initiation of Breast Feeding

Abstract: Background: Immediately after birth, the newborn should be placed in Skin-to-Skin Contact (SSC) with their mothers for at least an hour, and mothers should be assisted to initiate breastfeeding their newborns within the first half-hour. Objective is to explore the effect of skin-toskin contact between mothers and newborns at birth on temperature, oxygen saturation, and initiation of breast feeding. Method: A quasi-experimental design was utilized on the current study. Sample and setting: 300 mothers and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…[39][40][41][42] Neonatal transition to extrauterine life with and without skin-toskin contact has also been studied with babies from 25+ weeks and 1000+ g. As measured by parameters such as temperature, blood glucose levels and oxygen saturation, research examining full-term infants' transition to extrauterine life has shown that skin-to-skin contact is safe and the optimal choice for the habitat of the newborn. 21,38,[43][44][45][46][47][48] Prematurely born infants, as well as those born with low birth weight, transition well in skin-to-skin contact. [49][50][51][52][53] Even in cases of operative birth, immediate skin-to-skin contact supports the safe transition of the newborn.…”
Section: Key Notesmentioning
confidence: 99%
“…[39][40][41][42] Neonatal transition to extrauterine life with and without skin-toskin contact has also been studied with babies from 25+ weeks and 1000+ g. As measured by parameters such as temperature, blood glucose levels and oxygen saturation, research examining full-term infants' transition to extrauterine life has shown that skin-to-skin contact is safe and the optimal choice for the habitat of the newborn. 21,38,[43][44][45][46][47][48] Prematurely born infants, as well as those born with low birth weight, transition well in skin-to-skin contact. [49][50][51][52][53] Even in cases of operative birth, immediate skin-to-skin contact supports the safe transition of the newborn.…”
Section: Key Notesmentioning
confidence: 99%